PENGENDALIAN BIAYA DAN JADUAL TERPADU PADA PROYEK KONSTRUKSI. - Sudarsana, Dewa Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008, 2012)
Cost, performance and time are the major constrain resources in project execution. The important action to find project objective with limited resources are planning, scheduling and controlling. “Earned Value” concept is a method to integrated project cost and project schedule controlling. This method informed the project performanced in period reporting and to predict the total project cost completion and the project time completion based on performances indicator reporting. In case study on periodic 91st day reporting at ”Pembangunan Gedung Instalasi Rehabilitasi Medik” Center Public hospital Sanglah, the progress information such as Planed Value (PV)= IDR 1,4325 billion, Earned Value (EV) = IDR 1,3747 billion and Actual Cost (AC)= IDR 1,3598 billion. In this report the cost project performance had profit (Cost Varian, CV = + IDR 0,01 billion and Cost Performed Index ,CPI=1,01>1). But the schedule performanced project has been delayed (Schedule Varian, SV = - IDR 0.06 billion and Schedule Performmance Index, SPI =0,96 <1). If this project performanced continued until the project completion, the project cost completion has been estimated about IDR 2,8683 billion, that is under the budget (< IDR 2.8998 billion). However, the estimated project schedule required 129 days, which showed the project schedule will be delayed 2 days from the schedule plan.
Keywords: kinerja, jadual, biaya, nilai hasil, varian, indek